2018
DOI: 10.1038/s41598-018-20413-1
|View full text |Cite
|
Sign up to set email alerts
|

The Charging Events in Contact-Separation Electrification

Abstract: Contact electrification (CE)—charging of surfaces that are contacted and separated, is a common phenomenon, however it is not completely understood yet. Recent studies using surface imaging techniques and chemical analysis revealed a ‘spatial’ bipolar distribution of charges at the nano dimension, which made a paradigm shift in the field. However, such analyses can only provide information about the charges that remained on the surface after the separation, providing limited information about the actual course… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 46 publications
0
34
0
Order By: Relevance
“…During the motion process (sliding or separation), opposite charges on the surface of materials are produced, whose amount will significantly increase if the surface area increases and changes according to the different composition and structure of materials [24,25]. Several studies have been conducted to understand the charge formation mechanisms, and they also provided the basis for measurements standards [26][27][28]. In another work, Zou et al [29] demonstrated how to measure triboelectricity by using several polymers as examples.…”
Section: Introductionmentioning
confidence: 99%
“…During the motion process (sliding or separation), opposite charges on the surface of materials are produced, whose amount will significantly increase if the surface area increases and changes according to the different composition and structure of materials [24,25]. Several studies have been conducted to understand the charge formation mechanisms, and they also provided the basis for measurements standards [26][27][28]. In another work, Zou et al [29] demonstrated how to measure triboelectricity by using several polymers as examples.…”
Section: Introductionmentioning
confidence: 99%
“…The concept of “effective work function” has been proposed and relates the transfer of species from high-energy states to a low energy surface during contact charging of insulators ( 10 ). Unlike metals, tribo-charging of insulators involves not only the exchange of electrons, but also of ions and material ( 11 , 12 ). The relative contribution of each mechanism depends upon the mode of contact and stresses generated within the materials.…”
Section: Introductionmentioning
confidence: 99%
“…The relative contribution of each mechanism depends upon the mode of contact and stresses generated within the materials. The resulting net charge is a consequence of the balance between the contribution of the negative and positive species ( 11 , 12 ). After contact, the acquired charge will dissipate (decay) at a rate specific to the material and environment ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, unidirectional electron transfer that is justified by charge formation through bond breaking helps in understanding the underlying mechanism. [ 44,58–60 ]…”
Section: Triboelectric Nanogenerators In Briefmentioning
confidence: 99%